Identifying monetary policy rules in South Africa with inflation expectations and unemployment - Shannon Bold; Laurence Harris (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper investigates whether a Taylor rule accurately describes the South African Reserve Bank's reaction function in setting interest rates using quarterly data, covering the period since inflation targeting was formally adopted in 2000. The classic Taylor rule is modified to determine whether the South African Reserve Bank takes into account inflation expectations and labour market conditions. Our findings indicate that a modified Taylor rule does describe the South African Reserve Bank's policy rate adjustments. Our estimates of the modified rule yield two significant findings: the South African Reserve Bank's policy rate decisions respond to expected inflation (rather than current inflation), and its relationship to real economy fluctuations is evident in measures of labour market conditions rather than output gap variables. We conclude that under inflation targeting, South Africa's monetary policy has had a forward-looking inflation target that is pursued flexibly in the light of labour market conditions.
Keywords: E43; E52; E58; J69; 330; employment; labour; monetary policy; output gap; South Africa; Taylor rule; unemployment gap